Firm size and debt maturity as indirect determinants of capital structure: evidence form European panel data. Issue 18 (24th October 2018) - Koralun-Bereźnicka, Julia
ABSTRACT: The study aims at verifying whether the firm size and debt maturity affect the relationship between capital structure and its main determinants. Using panel data models, the impact of the primary factors on leverage is compared across three size groups of firms and for different measures of debt in order to identify the size effect and the debt maturity effect in these relationships. The study covers 11 EU countries during the period 2000–2013. Findings provide evidence that financing choices of small firms provide more support for the pecking-order theory, whereas medium and large-sized firms tend to follow the trade-off predictions on leverage. It also appears that the trade-off theory is more applicable for short-term debt, while pecking order – for long-term debt.